Correlation of P-wave dispersion with insulin sensitivity in obese adolescents. (8th April 2016) - Sert, Ahmet; Aslan, Eyup; Buyukınan, Muammer; Pirgon, Ozgur
Abstract: Background: P-wave dispersion is a new and simple electrocardiographic marker that has been reported to be associated with inhomogeneous and discontinuous propagation of sinus impulses. In the present study, we evaluated P-wave dispersion in obese adolescents and investigated the relationship between P-wave dispersion, cardiovascular risk factors, and echocardiographic parameters. Methods: We carried out a case–control study comparing 150 obese adolescents and 50 healthy controls. Maximum and minimum P-wave durations were measured using a 12-lead surface electrocardiogram, and P-wave dispersion was calculated as the difference between these two measures. Echocardiographic examination was also performed for each subject. Multivariate linear regression analysis with stepwise variable selection was used to evaluate parameters associated with increased P-wave dispersion in obese subjects. Results: Maximum P-wave duration and P-wave dispersion were significantly higher in obese adolescents than control subjects (143±19 ms versus 117±20 ms and 49±15 ms versus 29±9 ms, p<0.0001 for both). P-wave dispersion was positively correlated with body mass index, waist and hip circumferences, systolic and diastolic blood pressures, total cholesterol, serum levels of low-density lipoprotein cholesterol, triglycerides, glucose, and insulin, homoeostasis model assessment for insulin resistance score, left ventricular mass, and left atrial dimension. P-wave dispersion was negatively correlated with high-density lipoprotein cholesterol levels. By multiple stepwise regression analysis, left atrial dimension (β: 0.252, p=0.008) and homoeostasis model assessment for insulin resistance (β: 0.205; p=0.009) were independently associated with increased P-wave dispersion in obese adolescents. Conclusions: Insulin resistance is a significant, independent predictor of P-wave dispersion in obese adolescents.